Perbandingan Tingkat Likuiditas Sebelum Dan Sesudah Diterapkan Kebijakan Restrukturisasi Kredit (Studi Pada BPR Sekabupaten Gianyar) - Gusti Ayu Yuni Astari; Luh Gede Kusuma Dewi (Universitas Pendidikan Ganesha, 2022)
The purpose of this study is to verify the differences in the average liquidity level of Regular Banks as measured by Cash Ratio and Loan to Asset Ratio. To know the changes that have occurred before and after the implementation of the credit restructuring policy at the Rural Bank in Gianyar district registered with the OJK. There are 25 Rural Banks in Gianyar Regency registered with the OJK. The data used is secondary data in the form of financial statements in the third quarter of 2019 before the policy, and the third quarter of 2020 is after the policy. Based on the results of the hypothesis test by using Paired Sample t-Test. Shows the results in the period before and after the implementation of the credit restructuring policy was applied. A variable liquidity ratio experienced significant average changes, the variable is Cash Ratio. While the other variable has been researching, such as the Loan to Asset Ratio did not significant changes in average between before and after credit restructuringat the Rural bank. Keywords : Debt Restructuring, Cash Ratio, Loan to Aset Ratio, Rural Bank.